(untitled) (Journal of Nepal Geological Society, 1982)
The Pokhara Valley, a typical intramontane basin in the Nepal Himalayas, is spread around the midstream of the Seti Khola. It is filled with a large volume of gravelly deposits brought mostly from the Annapurna Himal, and splendid river terraces are present. Thus the Pokhara Valley is endowed with excellent conditions for the Quaternary chronological study of the Himalayas. Quaternary deposits in the valley are divided into nine stratigraphic units. Among them, the Ghachok and Pokhara Formations are most prominent, forming conspicuous accumulation terraces named the Pokhara and Ghachok Terraces. So far these accumulations were cosidered to have taken place during the glacial ages. In this study, however, the Pokhara Formation was dated by radiocarbon method to prove that the accumulation occurred in the late Holocene. Hagen (1969) considered that the Pokhara Valley, as well as the Kathmandu Valley, was once occupied by a single huge lake, and his hypothesis has many followers in spite of Gurung (1970)’s refutation. According to the present study, however only marginal lakes were formed due to damming of tributaries, and the possibility of the existance of a single huge lake in the Pokhara Valley is ruled out.